Д. Т. Березовець та Нетайлівський могильник салтівської культури: відкриття, сучасні дослідження, здобутки - Аксьонов, В.С. (Археологія і давня історія України, 2021)
У статті представлені попередні результати останніх років дослідження Нетайлівського
ґрунтового могильника салтівської культури,
який було відкрито у 1959 р. експедицією на чолі з
Д. Т. Березовцем. У роботі уточнюються висновки
дослідника відносно специфіки поховального обряду, хронології некрополя та етнічної належності
населення, яке його залишило. Наголошується, що
первинним місцем проживання населення, яке залишило Нетайлівський могильник, були райони
Північно-Східного Кавказу. Peculiarity of the Netailivka burial ground, noted
by its discoverer D. T. Berezovets, is the total predominance
of burials where the bones of the buried people
are completely absent. At the same time the burials
often contain grave goods located in the places when
the bodies of the deceased should have been lied. This
fact allowed D. T. Berezovets to suppose that initially
the burial was performed on the surface of the earth
where the body was exposed to natural factors and
only after that it was re-buried into a pit. However,
the researches of recent years show that burials were
made in full accordance with the funeral rite of the
Proto-Bulgarian population of the Saltiv culture. The
absence of human remains in most of the burial pits
should be associated with the specific hydrological conditions
prevailing at the site of the necropolis in the
post-Saltiv period. In a number of burials of the burial
ground the later activity in the burial pits, associated
with ritual actions performed in ancient times, were
recorded. These actions testify the existence of the socalled
«final ceremony» among the Netailivka people,
the holding of which meant the end of mourning for
the deceased person and made the death of a relative
complete and final for the living.
The study of the chronological markers of the site
made it possible to attribute the time of the burial ground
to the stage of the formation of the Saltiv culture in the
region and to date the earliest burials of the necropolis
to the 740—790 AD. The set of decorations and brooches
from early burials shows that the original area of the migration
of this population was the North-Eastern Caucasus
(the territory of modern Chechnya and Dagestan).
The location of the horse remains in the burials of the
horsemen indicates the mixed Turkic-Ugric character of
the population, which was part of the tribal union of the
«Bulgars». The date of the burial ground and the probable
area of residence of the population which made it,
allows us to identify the «Netailivka» people with the
representatives of the nomadic Bulgar union known
from literary sources as «Sabirs / Savirs».